2016
DOI: 10.1353/aaa.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Expanse of Archaeological Remains at Nalanda: A Study Using Remote Sensing and GIS

Abstract: Historical records suggest that Nalanda was a Buddhist monastery of considerable repute with immense physical dimensions, which remained in existence from the fourth/fifth century until at least the end of the twelfth. This study investigates the area around Nalanda for evidence of human activity at such spatiotemporal scales using satellite images. Among its finds are: the site is much larger than the property protected by the Archaeological Survey of India; there is evidence of additional temples and monaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In some cases, these measurements may help identify sites with potential for further exploration. As an example, the potential for investigating the archaeological mound under Begumpur (north of Nalanda) was confirmed by navigating to the precise location using a handheld device 40 . Data (in the form of exact tracks and points) recorded from such ground surveys can help in documenting, organizing and analysing field information, reducing the labour and time involved while increasing accuracy compared to traditional methods, which involved making detailed notes with approximate directions, distances and reference points.…”
Section: Global Navigation Satellite Systemsmentioning
confidence: 98%
“…In some cases, these measurements may help identify sites with potential for further exploration. As an example, the potential for investigating the archaeological mound under Begumpur (north of Nalanda) was confirmed by navigating to the precise location using a handheld device 40 . Data (in the form of exact tracks and points) recorded from such ground surveys can help in documenting, organizing and analysing field information, reducing the labour and time involved while increasing accuracy compared to traditional methods, which involved making detailed notes with approximate directions, distances and reference points.…”
Section: Global Navigation Satellite Systemsmentioning
confidence: 98%
“…Studies at other sites have revealed that regions of archaeological interest can extend significantly beyond protected areas 31 . Hence, this study used satellite imagery to examine the region surrounding the protected area.…”
Section: Sarnathmentioning
confidence: 99%
“…Although the wider manifestation of these patterns beyond the spatially restricted study area thus remains unknown, the resulting dataset is important for assessing text-driven theories regarding modes of interaction between monastic and lay populations, and offers useful parallels to similar, although more broadly dispersed patterns documented during the SSP [1][2][3]40,41 . In recent years, other similar projects focusing on historical socio-economic, agrarian and religious landscape dynamics have proliferated, from those dealing with Buddhist contexts 6,[42][43][44][45][46] , to those more aligned with later Hindu traditions [47][48][49] .…”
Section: Survey Archaeology In the Indian Subcontinentmentioning
confidence: 99%
“…Finally, restricted access to aerial photography and high-resolution maps was until recently a deterrent against intensive gridding methods 22 . Since 2006, various projects have capitalized on the availability of free satellite imagery such as Google Earth with varying aims and results [4][5][6] . In northwest India, the Rakhigarhi 53 and Ghaggar Hinterland Surveys 54 , through the use of remote sensing and GPS-based mapping enabled calibration of earlier village-to-village survey data 23,24 .…”
Section: Extensive Versus Intensive Surveymentioning
confidence: 99%
See 1 more Smart Citation